Survival analysis after stereotactic ablative radiotherapy for early stage non-small cell lung cancer: a single-institution cohort study - Resova, Kamila; Knybel, Lukas; Parackova, Tereza; Rybar, Marian; Cwiertka, Karel; Cvek, Jakub (Radiation oncology (London, England), 2024)
BACKGROUND: Stereotactic ablative radiotherapy (SABR) is the standard treatment for medically inoperable early-stage non-small cell lung cancer (ES-NSCLC), but which patients benefit from stereotactic radiotherapy is unclear. The aim of this study was to analyze prognostic factors for early mortality. METHODS: From August 2010 to 2022, 617 patients with medically inoperable, peripheral or central ES-NSCLC were treated with SABR at our institution. We retrospectively evaluated the data from 172 consecutive patients treated from 2018 to 2020 to analyze the prognostic factors associated with overall survival (OS). The biological effective dose was > 100 Gy10 in all patients, and 60 Gy was applied in 3-5 fractions for a gross tumor volume (GTV) + 3 mm margin when the tumor diameter was < 1 cm; 30-33 Gy was delivered in one fraction. Real-time tumor tracking or an internal target volume approach was applied in 96% and 4% of cases, respectively. In uni- and multivariate analysis, a Cox model was used for the following variables: ventilation parameter FEV1, histology, age, T stage, central vs. peripheral site, gender, pretreatment PET, biologically effective dose (BED), and age-adjusted Charlson comorbidity index (AACCI). RESULTS: The median OS was 35.3 months. In univariate analysis, no correlation was found between OS and ventilation parameters, histology, PET, or centrality. Tumor diameter, biological effective dose, gender, and AACCI met the criteria for inclusion in the multivariate analysis. The multivariate model showed that males (HR 1.51, 95% CI 1.01-2.28; p = 0.05) and AACCI > 5 (HR 1.56, 95% CI 1.06-2.31; p = 0.026) were significant negative prognostic factors of OS. However, the analysis of OS showed that the significant effect of AACCI > 5 was achieved only after 3 years (3-year OS 37% vs. 56%, p = 0.021), whereas the OS in one year was similar (1-year OS 83% vs. 86%, p = 0.58). CONCLUSION: SABR of ES-NSCLC with precise image guidance is feasible for all medically inoperable patients with reasonable performance status. Early deaths were rare in our real-life cohort, and OS is clearly higher than would have been expected after best supportive care.
Keywords: analýza přežití; Retrospective Studies; Survival Analysis; Cohort Studies; výsledek terapie; SBRT; mužské pohlaví; nádory plic; malobuněčný karcinom plic; Radiosurgery; kohortové studie; radiochirurgie; Neoplasm Staging; nemalobuněčný karcinom plic; retrospektivní studie; Humans; ES-NSCLC; Carcinoma, Non-Small-Cell Lung; staging nádorů; Overall survival; Small Cell Lung Carcinoma; Treatment Outcome; Lung Neoplasms; lidé; Male